Correlates of reproductive coercion among college women in abusive relationships: baseline data from the college safety study - Grace, Karen Trister; Perrin, Nancy A.; Clough, Amber; Miller, Elizabeth; Glass, Nancy E. (Journal of American college health, 2022)
Objective The purpose of this study was to examine correlates of reproductive coercion (RC) among a sample of college women in abusive relationships. Participants: 354 college students reporting a recent history of intimate partner violence (IPV). Methods: This study examines baseline data from a randomized controlled trial testing effectiveness of an interactive safety decision aid (myPlan). Results: Almost a quarter (24.3%) of the sample reported RC. Associated factors included races other than White (p = 0.019), relationship instability (p = 0.022), missing class due to relationship problems (p = 0.001), IPV severity (p < 0.001), technology abuse (p < 0.001), traumatic brain injury-associated events (p < 0.001), and depression (p = 0.024). Conclusions: RC was a significant predictor of depression, with implications for providers working with abused college women regarding the need for mental health services concurrent with IPV/RC services. A larger proportion of women who experienced RC sought help from a healthcare provider for contraception, which suggests intervention opportunities for college health providers.